2016
DOI: 10.1016/j.pscychresns.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Externalizing personality traits, empathy, and gray matter volume in healthy young drinkers

Abstract: Externalizing psychopathology has been linked to prefrontal abnormalities. While clinically diagnosed subjects show altered frontal gray matter, it is unknown if similar deficits relate to externalizing traits in non-clinical populations. We used voxel-based morphometry (VBM) to retrospectively analyze the cerebral gray matter volume of 176 young adult social to heavy drinkers (mean age= 24.0 ± 2.9, male= 83.5%) from studies of alcoholism risk. We hypothesized that prefrontal gray matter volume and externalizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 82 publications
0
9
1
Order By: Relevance
“…In morphometric studies, alcohol use is correlated with gray matter shrinkage in the cortical striatal limbic circuits, suggesting chronic, neurotoxic effects of alcohol on cerebral structures (Yang et al, 2016). On the other hand, evidence accumulates that cerebral gray matter volumes may represent neural markers of psychological traits that dispose individuals to problem drinking (Charpentier et al, 2016, Holmes et al, 2016, Luciana et al, 2013, Schilling et al, 2013). Thus, whether changes in cerebral morphometry reflect primarliy the effects of alcohol or may represent a trait marker of individual vulnerability to problem drinking remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In morphometric studies, alcohol use is correlated with gray matter shrinkage in the cortical striatal limbic circuits, suggesting chronic, neurotoxic effects of alcohol on cerebral structures (Yang et al, 2016). On the other hand, evidence accumulates that cerebral gray matter volumes may represent neural markers of psychological traits that dispose individuals to problem drinking (Charpentier et al, 2016, Holmes et al, 2016, Luciana et al, 2013, Schilling et al, 2013). Thus, whether changes in cerebral morphometry reflect primarliy the effects of alcohol or may represent a trait marker of individual vulnerability to problem drinking remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, OFC, IFG, and rostral MFG are heavily implicated in top-down regulatory processes, including emotion regulation, decision-making, and inhibition, that are crucial for regulating aggressive behaviors ( Bechara et al, 2000 , Blair and Lee, 2013 ). Although the relevance of occipital cortices for aggression is less clear, emerging evidence has linked activity in the visual cortex to engagement in violent and antisocial behaviors ( Bertsch et al, 2013 , Charpentier et al, 2016 ). For example, visual perception is crucial for facial expression processing, which is necessary for developing empathy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, reduced cortical thickness in the right pericalcarine cortex has been linked to associated psychological processes, such as sensation seeking and engagement in risky behaviors ( Holmes et al, 2016 , Miglin et al, 2019 ). Thus, visual processing may indirectly impact the likelihood to display aggressive tendencies ( Charpentier et al, 2016 , Horan et al, 2014 ). Together, the present results are consistent with literature linking both frontal and occipital cortices to behaviors marked by impulse control and decision-making disruptions.…”
Section: Discussionmentioning
confidence: 99%
“…The sample consisted of 148 young (21-35 years) social-to-heavy drinking male subjects from several alcoholism risk studies. Structural imaging data from 88 subjects were included in the study relating externalizing personality traits and gray matter volume (Charpentier et al, 2016), with a subset of these 88 subjects also reported in the studies of dopaminergic responses to beer (Oberlin et al, 2013 and 28, respectively), and regional cerebral blood flow (Weafer et al, 2015, n=44). Subjects' demographic and a risk for alcoholism-related characteristics are summarized in Table 2.…”
Section: Data and Preprocessingmentioning
confidence: 99%